Assessment of physicochemical parameters and heavy metals concentration of leachates from dumpsite around Idemili River, Obosi Nigeria - Dibua, N.A.; Okoye, E.C.S.; Egudu, N.A.; Chibueze, C.B.; Azuka, C.P.; Ojeah, I.K.; Nwosu, O.K. (Archives of Agriculture and Environmental Science, 2025)
Leachates originating from solid waste dumpsites pollute water bodies, especially in Nigerian urban areas. This study aimed to assess the concentrations of heavy metals and physicochemical parameters in leachates from dumpsite around the Idemili River in Obosi, Nigeria. Physicochemical parameters (pH, temperature, EC, TDS, DO, BOD, turbidity, chloride, nitrate, phosphate, sulphate), heavy metals (Zn, Pb, Cd, Cu, Fe, As) and bacteriological parameters (total and faecal coliforms) were analyzed in leachate and Idemili River water. ANOVA, Tukey’s post-hoc and Pearson correlation were applied to find spatial variations and relationships between physicochemical properties and heavy metals concentration in leachate and water samples. Results revealed significant (p<0.05) contamination, with EC, sulphate, phosphate, nitrate, Fe, Cd and Pb in leachate samples exceeding WHO/NSDWQ limits. Leachate contained significantly higher levels of Fe (4.430±3.231 mg/L), As (4.455±3.1465 mg/L) and Cd (2.8783±2.794 mg/L), suggesting potential leachate infiltration, thereby influencing water quality. Also the leachate and water samples had elevated levels of total and faecal coliforms, exceeding the WHO standards of 10 cfu/mL and 0 cfu/mL, respectively. Results also revealed significant spatial variations in the physicochemical, heavy metals, and bacteriological parameters across various sampling points in leachate and water samples. Therefore, water samples from Idemili River are unsafe for human consumption, and aquatic ecosystems, due to leachates infiltration. It is recommended that governments should adopt inclusive approaches to reducing amount of wastes reaching dumpsites.